The alchemist's shadow - Funaro, Gregory (Funaro, Gregory. Watch Hollow (Series), 2020)
A great evil enters Blackford House, transforming it into a dangerous labyrinth and forcing Lucy and Oliver Tinker to join forces with the Kojima twins, who claim to be the true owners of the Tinker's home.